2018
DOI: 10.1002/mame.201800601
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Gradient Morphologies and Anisotropic Surface Patterns in Polymer Blends

Abstract: Gradient morphologies and surface patterns can provide a template for smart materials with tailored local properties. Fabricating such structures in a onestep melt-extrusion process will be most beneficial as they usually require several manipulation steps. In this study, gradient morphologies are developed by melt-spinning matrix-dispersed polypropylene/polystyrene blends as a template system and dynamic control of their formation is achieved, which further leads to anisotropic surface patterns. Cross and lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 55 publications
(72 reference statements)
3
27
0
Order By: Relevance
“…Cox and Grace predicted the droplet size during simple melt processing and proposed the deformation of a droplet to be normalD=()Ca2[]19p+16/16p+16()19pCa/402+11/2 for all viscosity ratios under shear flow. Theoretically, a high viscosity ratio will result in large deformed droplets and a coarse morphology, whereas a low or matching viscosity ratio could result in fine fibrils and uniform morphology . In most experimental cases, the dispersed phase was found to be finer for viscosity ratios less than one ( p ≤ 1) than that for viscosity ratios larger than one ( p > 1) .…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Cox and Grace predicted the droplet size during simple melt processing and proposed the deformation of a droplet to be normalD=()Ca2[]19p+16/16p+16()19pCa/402+11/2 for all viscosity ratios under shear flow. Theoretically, a high viscosity ratio will result in large deformed droplets and a coarse morphology, whereas a low or matching viscosity ratio could result in fine fibrils and uniform morphology . In most experimental cases, the dispersed phase was found to be finer for viscosity ratios less than one ( p ≤ 1) than that for viscosity ratios larger than one ( p > 1) .…”
Section: Introductionmentioning
confidence: 98%
“…By applying similar ideas to synthetic immiscible polymers, desirable morphologies and properties can be achieved by controlling the external field (e.g., gradient temperature field and electric fields), polymer diffusion in interpenetrating polymer networks, and phase separation in multicomponent blends . Recently, we produced polymer fibers with gradient microstructures by tuning melt processing parameters and capillary die design . We showed that gradient fibers with fine thin fibrils in the surface region and large slightly‐deformed droplets in the central region can be achieved by special capillary design .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations